Effect of packing factor on electrical and overall energy generation through low concentrated photovoltaic thermal collector in composite climate condition. (2020) - Tripathi, Rohit; Bhatti, T.S.; Tiwari, G.N.
Abstract: In present research paper, one attempt has been carried out to show the performance of photovoltaic thermal collector with the effect of packing factor. Earlier many studies has been investigated on photovoltaic thermal collector design, parameters, climate and weather condition, exergoeconomic and enviroeconomic analysis. But here, effect of packing factor has been shown in results and it is concluded, electrical and overall exergy increases when packing factor increases, and, thermal energy and overall energy increases when packing factor decreases. Now according to demand of electrical and thermal energy, this packing factor can be optimized with collector size. In present study, the most suitable packing factor has been optimized as 0.5 where, collector area is 1 m 2 . At this value of packing factor, the maximum outlet water temperature with flow rate 0.01 kg/s has been observed 45 0 C in a clear day, month of January at New Delhi. The maximum daily electrical, thermal, overall exergy gain have been obtained as 3.97, 1.86 and 5.83 kWh, respectively.